Instalasi Pembangkit Listrik Tenaga Surya (PLTS) sebagai Sumber Energi Listrik Pada BUMDes Air Isi Ulang Desa Nosar Kabupaten Aceh Tengah - Alfisyahrin Alfisyahrin; Zalmi Zalmi; Alfiansyah Yulianur BC; Syukriyadin Syukriyadin (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
This community service program aims to provide a sustainable energy solution through the installation of a Solar Power Plant (PLTS) for the Refill Water Village-Owned Enterprise (BUMDes) in Nosar Village, Central Aceh Regency. The program addresses high operational costs caused by dependence on conventional electricity. The implementation method involves systematic stages, including needs identification, community organization, technical training, PLTS installation, and initial monitoring and evaluation. The results show significant positive impacts, including reduced operational costs for BUMDes, increased energy independence, and the transfer of technical knowledge to the community. BUMDes managers now possess the capability to operate and maintain the PLTS system independently, ensuring the program's sustainability over the long term. Activities such as training sessions, installations, and system trials were thoroughly documented to strengthen the program's validity. By adopting a participatory and community-empowerment approach, this program delivers immediate benefits to its partners while establishing a replicable model for renewable energy development in other regions. The program demonstrates that technological solutions can serve as catalysts for sustainable economic and social change.